Diplomatic security : a comparative analysis - Cusumano, Eugenio; Kinsey, Christopher (Stanford University Press, 2019)
The safety of diplomats has animated recent public & political debates. As diplomatic personnel are increasingly targeted by terrorism & political violence while overseas, sending states are augmenting host nations' security measures with their own. Protective arrangements range from deploying military, police, & private security guards to relocating embassies to suburban compounds. Yet, reinforced security may also hamper effective diplomacy & international relations. Scholars & practitioners from around the world bring to light a large body of empirical information in 'Diplomatic Security'.